MANAGING CREATIVITY: HUMAN RESOURCE STRATEGIES FOR TALENT DEVELOPMENT AND INNOVATION IN CULTURAL AND CREATIVE INDUSTRIES - Dhawan, Neha; Gupta, Vidhu; Sharma, Ankita; Singh, Bikram; Malik, Rupina Popli; Fernandes, Dr. Jessica (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This is a conceptual paper that discusses the importance of human resource management strategies in promoting creativity and innovation in cultural and creative industries with specific reference to the visual and performing arts industry. Basing on the componential theory of creativity, resource-based view, and knowledge creation theory, the study derives an extensive framework between the HRM practices and talent development, employee creativity, and the innovation outputs. It contends that strategic HR interventions, including talent acquisition, ongoing training, performance management, and motivation, will increase the level of creative abilities by employees, as well as intrinsic motivation, thus leading to both artistic as well as organizational innovation. The article also highlights the moderating role of the context of the creative industry that is typified by the presence of artistic and commercial goals and the rising digital transformation. The study acting as a combination of the input of HRM and creativity literature and the cultural background presents the contribution to theoretical knowledge and provides pragmatical suggestions on the successful management of creative talent in active and innovation driven management.